Feedback as Scaffolded Instruction in the Assessment of L2 Writing Tasks - Zena Abu Shakra (European Scientific Journal, ESJ, 2023)
This study focuses on exploring the relationship between the concept of learner autonomy and foreign language writing feedback. A sample of 4 writing conferences were transcribed in order to carry out spoken discourse analysis based on the Burton (1981) model, which is directly derived from the Sinclair and Coulthard (1975) model. The aim was to linguistically ascertain the instructor’s attempt to stimulate learner autonomy through scaffolding based on the three principles of Little (2000). It was important to also take into cognizance the concomitant discourse that accompanies such an attempt in an effort to compare the findings with those observed in the initial study done on conferences, which involved more holistic feedback on the whole essay. The design also made use of short retrospective self-reports where L2 writers recorded their thoughts and comments directly following the feedback they received in each conference. This study builds on a previous study which demonstrated how writing instructors often mistakenly presuppose that learners have reached their perspective on a writing revision. This happens at a point much earlier than expected when in fact, learners appear to be cognitively engaged at a point much later than when they claim understanding of the revision being made. The present study expands on the original by comparing the quality of discourse observed in the previous study, which involved more holistic feedback on writing, especially when feedback is more focused and limited to one section of writing. Findings suggest that minimizing feedback results in instructor discourse that is more superior as a scaffolding instrument, while learner discourse shows more evidence of metacognitive activity and reflection. Paradoxically, curtailing feedback which facilitates learning and task acquisition during the assessment of writing actually renders it more scaffolded in nature, thus resulting in more positive outcomes for both the instructor and L2 learner. The theoretical and pedagogical implications of this are discussed extensively.